Lucky women in unlucky cohorts - Berniell, Inés,Gasparini, Leonardo,Marchionni, Mariana,Viollaz, Mariana (CEDLAS, Universidad Nacional de la Plata, 2022)
This paper assesses gender differences in the effects of adverse conditions at labor-market entry in a developing region. Using harmonized microdata from national household surveys for 15 Latin American countries, we build a synthetic panel of cohorts that potentially transition from school to work and observe their labor market outcomes 10 years later. We find that men who faced higher unemployment rates at ages 18-20 suffer a negative effect on employment at ages 27-30. In contrast, women from those same unlucky cohorts have higher employment rates and earnings. Our results are consistent with women acting as secondary workers in downturns. We also find that women from unlucky cohorts control a larger share of family income and are more likely to be the head of household 10 years after labor market entry, and that adverse initial labor market conditions are correlated to more egalitarian perceptions about gender roles later in life.
10419/274106
Keywords: Graue Literatur; crises; unemployment; scarring effects; gender; secondary worker; Latin America